PROSEDUR PERUBAHAN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 SEBELUM DAN SESUDAH PERUBAHAN - Beby Reschentia; Mexsasai Indra; Junaidi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
All of constitution always have a change clausul in the text. It same with constitution of Indonesia that exist in article 37 constitution 1945. But unfortunatelly, because of the power of politic in the new era that build extrem autority had been make the constitution be sacred. Except passed by referendum that is decision of people‟s Consultative Council No.IV/MPR/1983 and Civil Law number 5 1985. Author‟s opinion in practis the changes to constitution 1945 is not suitable with the written on the constitution. In the reformation euphoria of Soeharto then make a claim to do an amendment close to the reality that is implementation in 1999-2002 (the first, the second, the third, and the fourth changes ). Author have an opinion there are the developments in the law section that have a relation with constititution 1945 changes procedure. The core is how the change on the theory and the constitution also implementation and practice in Indonesia. The last are flexibility or rigid of the constitution categorized. Because if we talking about amendment almost relevance with the grade of easy or difficult of constitution is changed. Therefor based on the amendment procedure the author interest to make a correlation the suitable with the general principles of the constitution amendment in the generally modern constitution in the practice of constitution in Indonesia.Keyword: Procedure – Amendment – Constitution 1945